Nanoscale Intergranular Corrosion and Relation with Grain Boundary Character as Studied In Situ on Copper. Issue 11 (7th September 2018) - Bettayeb, Mohamed; Maurice, Vincent; Klein, Lorena H.; Lapeire, Linsey; Verbeken, Kim; Marcus, Philippe
Abstract : The initiation of intergranular corrosion at various types of grain boundaries (GBs) was studied at the nanometer scale on microcrystalline copper in 1 mM HCl aqueous solution. In situ Electrochemical Scanning Tunneling Microscopy (ECSTM) and Electron Back-Scatter Diffraction analysis of the same local microstructural region were combined using an innovative methodology including micro marking performed with the STM tip. The results demonstrate that electrochemically-induced intergranular dissolution, at the surface termination of GBs, is dependent on the grain boundary character. It is found that random high angle boundaries as well as Σ9 coincidence site lattice (CSL) boundaries are susceptible to nanoscale initiation of intergranular corrosion while for Σ3 CSL boundaries the behavior is dependent on the deviation angle of the GB plane from the exact orientation. For the Σ3 twins, a transition from resistance to susceptibility occurs between 1° and 1.7° of deviation as a result of the increase of the density of steps (i.e. misorientation dislocations) in the coincidence boundary plane. The work emphasizes the precision needed in the design of the grain boundary network in applications where intergranular corrosion or its initiation must be controlled at the nanoscale.